Respiratory intensive care units in Italy: a national census and prospective cohort study. Issue 5 (1st May 2001) - Confalonieri, M; Gorini, M; Ambrosino, N; Mollica, C; Corrado, A
Abstract : BACKGROUND: In Italy, respiratory intensive care units (RICUs) provide an intermediate level of care between the intensive care unit (ICU) and the general ward for patients with single organ respiratory failure. Because of the lack of official epidemiological data in these units, a two phase study was performed with the aim of describing the work profile in Italian RICUs. METHODS: A national survey of RICUs was conducted from January to March 1997 using a questionnaire which comprised over 30 items regarding location, models of service provision, staff, and equipment. The following criteria were necessary for inclusion of a unit in the survey: (1) a nurse to patient ratio ranging from 1:2.5 to 1:4 per shift; (2) availability of adequate continuous non-invasive monitoring; (3) expertise for non-invasive ventilation (NIV) and for intubation in case of NIV failure; (4) physician availability 24 hours a day. Between November 1997 and January 1998 a 3 month prospective cohort study was performed to survey the patient population admitted to the RICUs. RESULTS: Twenty six RICUs were included in the study: four were located in rehabilitation centres and 22 in general hospitals. In most, the reported nurse to patient ratio ranged from 1:2 to 1:3, with 36% of units reporting a ratio of 1:4 per shift. During the study period 756 consecutive patients of mean (SD) age 68 (12) years were admitted to the 26 RICUs. The highest proportion (47%) were admitted from emergency departments, 19% from other medical wards, 18% were transferred from the ICU, 13% from specialist respiratory wards, and 2% were transferred following surgery. All but 32 had respiratory failure on admission. The reasons for admission to the RICU were: monitoring for expected clinical instability (n=221), mechanical ventilation (n=473), and weaning (n=59); 586 patients needed mechanical ventilation during their stay in the RICU, 425 were treated with non-invasive techniques as a first line of treatment (374 by non-invasive positive pressure, 51 by iron lung), and 161 underwent invasive mechanical ventilation (63 intubated, 98 tracheostomies). All but 48 patients had chronic respiratory disease, mainly chronic obstructive pulmonary disease (COPD; n=451). More than 70% of patients (n=228) had comorbidity, mainly consisting of heart disorders. The median APACHE II score was 18 (range 1–43). The predicted inpatient mortality risk rate according to the APACHE II equation was 22.1% while the actual inpatient mortality rate was 16%. The mean length of stay in the RICU was 12 (11) days. The outcome in most patients (79.2%) admitted to RICUs was favourable. CONCLUSIONS: Italian RICUs are specialised units mainly devoted to the monitoring and treatment of acute on chronic respiratory failure by non-invasive ventilation, but also to weaning from invasive mechanical ventilation. The results of this study provide a useful insight into an increasingly important field of respiratory medicine.